2004
DOI: 10.1345/aph.1e134
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Hyperlipidemia Control with Daily Versus Twice-Weekly Simvastatin

Abstract: The twice-weekly regimen safely maintained most of the patients at their LDL-C goal level, and over half the patients found this regimen to be the same or easier to follow than a daily regimen. Large outcome studies evaluating this approach are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Studies evaluating the effect and tolerance of alternative statin dosing are limited. A limited number of trials have demonstrated efficacy with alternate-day statin dosing including a few anecdotal case reports,[1417] but till date no such trials have been conducted in India. The study reported here examines the effect and tolerance of every other day atorvastatin therapy in comparison to the established daily statin regimen in reduction of plasma LDL-C.…”
Section: Introductionmentioning
confidence: 99%
“…Studies evaluating the effect and tolerance of alternative statin dosing are limited. A limited number of trials have demonstrated efficacy with alternate-day statin dosing including a few anecdotal case reports,[1417] but till date no such trials have been conducted in India. The study reported here examines the effect and tolerance of every other day atorvastatin therapy in comparison to the established daily statin regimen in reduction of plasma LDL-C.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperlipidemia is an important risk factor leading to cardiovascular disease, which is a major cause of death in many countries and has arisen as a global health issue (Jain and others ). Because it was suggested that the appropriate control of the lipid levels in blood circulatory system might be a standard strategy to prevent cardiovascular disease (Mangin and others ), various anti‐hyperlipidemia agents, such as bile acid sequestrants (for example, cholestyramine), 3‐hydroxy‐3‐methylglutaryl coenzyme A reductase inhibitors (for example, statin), and fibric acid derivatives (for example, gemfibrozil) have been used. However, in some cases, the use of these agents has resulted in adverse effects such as hepatotoxicity, myopathy, or noncardiovascular death (Kashani and others ).…”
Section: Introductionmentioning
confidence: 99%